Development of Nature Studies and Technologies Competence in the Context-oriented Process of Learning Physics - Dzerviniks, Jānis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
As Latvia is in the single European economic space, more and more attention is paid to the development of nature studies and technologies Exactly nature studies teach pupils to observe nature and natural phenomena objectively, analyse and understand them, make conclusions and foresee results. Nature studies provide students everything what is needed to form and deepen their understanding of the surrounding world. It would facilitate pupils’ thirst for knowledge and a critical view, and reflect the link between an individual and nature. Qualitative learning process of nature studies at school enables pupils gain general basic knowledge and basic skills in the field of science, develop the competence of nature studies and technologies facilitating the process of pupils becoming technologically aware members of society and encouraging them for further movement deeper into the field of science and technologies. In order to arouse interest in nature studies and facilitate acquisition of knowledge with understanding there shall be used pedagogical approaches enabling transition from memorizing scientific facts to construction of knowledge in the ways understandable and meaningful to pupils. One of the opportunities is involving pupils in the learning process in the research of problems in natural sciences in the real life context. It means that the development of the competence of nature studies and technologies shall be facilitated in the context-oriented learning process. In Latvia in the field of nature studies didactics there are not sufficiently explored the issues about the understanding of the notion of context and implementation of context-based learning in physics. Thus, in the research reflected in the article there is analysed scientific literature on the theme mentioned above, the analytical judgments are based on the prior empirical researches as well as using the author’s personal pedagogical experience.